Analysis of Lead (Pb) In Street Vendors' Urine at Antang Market, Makassar - Santi Santi; Lisda Maulina (Helium: Journal of Science and Applied Chemistry, 2025)
Lead is a pollutant originating from motor vehicles. As a heavy metal, it is harmful to living organisms and may cause serious health problems. This study aimed to determine the levels of lead (Pb) in the urine of street vendors around the Antang market, Makassar.  This study used an atomic absorption spectrophotometer (AAS) to analyze lead levels in the urine of 10 street vendors who met the study criteria. The results of this study showed that of 10 respondents, 4 had lead levels below the standard threshold, and 6 exceeded it. The highest level was 0.28 mg/L. This suggests that prolonged exposure is associated with higher urinary lead levels.